2011
DOI: 10.1073/pnas.1012293108
|View full text |Cite
|
Sign up to set email alerts
|

Molecular vibration-sensing component in Drosophila melanogaster olfaction

Abstract: A common explanation of molecular recognition by the olfactory system posits that receptors recognize the structure or shape of the odorant molecule. We performed a rigorous test of shape recognition by replacing hydrogen with deuterium in odorants and asking whether Drosophila melanogaster can distinguish these identically shaped isotopes. We report that flies not only differentiate between isotopic odorants, but can be conditioned to selectively avoid the common or the deuterated isotope. Furthermore, flies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
219
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(244 citation statements)
references
References 42 publications
(51 reference statements)
18
219
1
6
Order By: Relevance
“…Earlier claims that human subjects can distinguish odors of acetophenone isotopomers (9,35) have been shown to be untrue (14,31). Recent studies indicate that Drosophila melanogaster can distinguish acetophenone isotopomers (36,37) and that Apis mellifera L., the honey bee, can be trained to discriminate pairs of isotopomers (38). These studies differ from earlier insect studies in which isotopomer discrimination was not found.…”
Section: Significancementioning
confidence: 84%
“…Earlier claims that human subjects can distinguish odors of acetophenone isotopomers (9,35) have been shown to be untrue (14,31). Recent studies indicate that Drosophila melanogaster can distinguish acetophenone isotopomers (36,37) and that Apis mellifera L., the honey bee, can be trained to discriminate pairs of isotopomers (38). These studies differ from earlier insect studies in which isotopomer discrimination was not found.…”
Section: Significancementioning
confidence: 84%
“…The Markov approximation amounts to replacing the state at time s in the integrand of Eq. (26) with the state at time t, changing variables such that s → t − τ , and taking the integral to infinity:…”
Section: Appendix: Derivation Of the Master Equationmentioning
confidence: 99%
“…may be possible to distinguish the scents of some very similar odorants, for example between those that are deuterated and non-deuterated. 26,30,37 It was suggested as early as 1938 that the sensing of vibrational spectra of molecules [38][39][40] -later proposed to occur via electron transfer 21,22 -could play an important role in olfaction, supplementing (rather than replacing) the existing lockand-key model. Recent work, focussing on constructing and exploring model systems that capture the important physical processes, 24,27 has shown that this is indeed a viable proposition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has even been extended to the rather extreme proposal that our sense of olfaction is based on vibrational modes, 88 which is clearly really problematic (see, e.g., Ref. 89), and will therefore not be examined here.…”
Section: Mode Coupling Dynamical Effects and Compressionmentioning
confidence: 99%